Tablice kanonów – symbolika dekoracji architektonicznej - Cichoń, Krzysztof (Acta Universitatis Lodziensis. Folia Historica, 2002)
This paper deals with the history of the development of canon tables in early medieval manuscripts. The author concentrates on the role of the architectural decoration of canon tables. This type of decoration was very important for the development of iconography, especially in Byzantium, where one can observe the tendency to expand the role of calligraphy on the cost of illumination. Canon tables were instrumental in propagation of the type oi composition (originating probably from astronomical codices of late antiquity) in which text is enclosed by an architectural frame. For the canon tables created after the 10th century characteristic is transition from tectonic to ornamental treatment of the frame. The motifs of antithetic animals (usually birds) and pair of trees placed next to the arcades are obligatory elements of the frame. This pattern deriving from the canon tables compositions belongs to the most widespread schemes in medieval illuminations.